Characteristics of subjective cognitive decline associated with amyloid positivity. Issue 10 (8th December 2021) - Janssen, Olin; Jansen, Willemijn J.; Vos, Stephanie J.B.; Boada, Merce; Parnetti, Lucilla; Gabryelewicz, Tomasz; Fladby, Tormod; Molinuevo, José Luis; Villeneuve, Sylvia; Hort, Jakub; Epelbaum, Stéphane; Lleó, Alberto; et al.
Abstract: Introduction: The evidence for characteristics of persons with subjective cognitive decline (SCD) associated with amyloid positivity is limited. Methods: In 1640 persons with SCD from 20 Amyloid Biomarker Study cohort, we investigated the associations of SCD‐specific characteristics (informant confirmation, domain‐specific complaints, concerns, feelings of worse performance) demographics, setting, apolipoprotein E gene ( APOE ) ε4 carriership, and neuropsychiatric symptoms with amyloid positivity. Results: Between cohorts, amyloid positivity in 70‐year‐olds varied from 10% to 76%. Only older age, clinical setting, and APOE ε4 carriership showed univariate associations with increased amyloid positivity. After adjusting for these, lower education was also associated with increased amyloid positivity. Only within a research setting, informant‐confirmed complaints, memory complaints, attention/concentration complaints, and no depressive symptoms were associated with increased amyloid positivity. Feelings of worse performance were associated with less amyloid positivity at younger ages and more at older ages. Discussion: Next to age, setting, and APOE ε4 carriership, SCD‐specific characteristics may facilitate the identification of amyloid‐positive individuals.